2012
DOI: 10.1002/sd.1554
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Reporting and Varieties of Capitalism

Abstract: The mixed results of previous empirical investigations on the relevance of firms' reporting on sustainable development could be due to the absence of a theoretical paradigm able to capture the differences across countries. We apply the varieties of capitalism approach on a sample of European listed banks from 2005 to 2011, to evaluate whether the different institutional contexts affect the value relevance of sustainability reporting in European stock markets. The results show that sustainability reporting is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 67 publications
1
22
0
1
Order By: Relevance
“…Bushman et al, 2004;Carnevale and Mazzuca, 2014;Frias-Aceituno et al, 2013;Hope, 2003;Ioannou and Serafeim, 2012). Common to these approaches is the argument that differences in nation-level institutionssuch as the political, financial or legal system -influence the level and type of corporate disclosure.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Bushman et al, 2004;Carnevale and Mazzuca, 2014;Frias-Aceituno et al, 2013;Hope, 2003;Ioannou and Serafeim, 2012). Common to these approaches is the argument that differences in nation-level institutionssuch as the political, financial or legal system -influence the level and type of corporate disclosure.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Most CSR reports are published following the guidelines issued by the Global Reporting Initiative (GRI, ). Indeed, many studies have analysed how companies follow them on a voluntary basis to issue a sustainability report (Hassan and Ibrahim, ), and the impact of this impact on company performance and market value (Carnevale et al , , Carnevale and Mazzuca, ), information asymmetries and capital constraints (Cheng et al , ) or firm reputation (Maignan, ). Some companies provide external assurance to these reports as a way of enhancing credibility, following the voluntary standards set by the International Federation of Accountants (IFAC) and AccountAbility (IAASB, ; AccountAbility, ; Belal, ; Zorio et al, ).…”
Section: Sustainable Development Csr Reporting and Analyst Forecastsmentioning
confidence: 99%
“…An analysis of literature on philanthropy gives evidence about differences among countries and considers that the varieties of capitalism, the altruistic culture of countries, and religion are among the causes for these differences. For example, Carnevale and Mazzuca (2014) found that pressures from stakeholders to disclose CSR activities are higher in coordinated market economies (such as Germany, Austria, Finland, and the Netherlands) than in liberal market economies (UK). This institutional perspective has also been used to explain differences according to whether the country is a welfare state or the religion in countries (Koos, 2012).…”
Section: Hypothesesmentioning
confidence: 99%